Interictal regional paroxysmal fast activity on scalp EEG is common in patients with underlying gliosis. Issue 5 (May 2018) - Dash, Gopal Krishna; Rathore, Chaturbhuj; Jeyaraj, Malcolm K.; Wattamwar, Pandurang; Sarma, Sankara P.; Radhakrishnan, Kurupath
Highlights: Regional paroxysmal fast activity is present in 25% of patients with drug resistant focal epilepsy. Regional paroxysmal fast activity is equally common in patients with gliosis and dysplasia. Perinatal injury with gliosis is common cause for paroxysmal fast activity in developing countries. Abstract: Objective: Interictal regional paroxysmal fast activity (RPFA) on scalp EEG is common in patients with focal cortical dysplasia (FCD). Little data exists regarding the presence of RPFA in other etiologies. Methods: We studied the association between RPFA and etiology on MRI in patients with drug resistant focal epilepsy undergoing presurgical evaluation in 2011. RPFA was defined as ≥3 consecutive spikes with a frequency of ≥10 Hz lasting ≥300 ms but <4 s. Results: 626 patients fulfilled the inclusion criteria. Of these, 138 (22%) patients had RPFA while rest had other interictal epileptiform discharges (IEDs). RPFA was located at posterior head region in 52.2% patients, frontal regions in 24.6% patients and over temporal regions in 17.4% patients. Focal gliosis (61, 44%) and FCD (27, 19%) were common etiologies in patients with RPFA. Compared to patients with other IEDs, patients with RPFA were more likely to have focal gliosis (61/138 vs. 39/488; p  < 0.0001) or FCD (27/138 vs 37/488; p  < 0.001) as the etiology of epilepsy. Conclusion: In developing countries, focal gliosis is more common than FCD as the underlying etiology in patients with RPFA on scalp EEG. Significance: Focal gliosis should be considered as one of the common substrate for RPFA on scalp EEG.